DNA and RNA - Hall, Linley Erin. 4 0 16; 5 (New York : Rosen Publishing, 2011)
Provides an introduction to deoxyribonucleic acid, or DNA, and ribonucleic acid, or RNA, and explains how they work together to make proteins.
Introduction to DNA -- DNA replication -- Introduction to RNA -- Transcription and translation -- Gene regulation -- Mutations for good and bad -- Recombinant DNA.
Includes bibliographical references (p. 74-76) and index.
6.2;Young Adult;Young Adult.
Keywords: 2 -- 0; 6; DNA;RNA -- 20 -- Juvenile literature.;Juvenile literature; 20; 2